Carbon sequestration of Hungarian forests by management system and protection status - Éva Király; Attila Borovics (Trees, Forests and People, 2024)
The Paris Agreement and the European Green Deal set ambitious climate change mitigation goals. In order to achieve these goals and offset the emissions of all other sectors significant additional carbon sequestration is needed in the land use sector. The capacity of the land use sector and especially forests to remove carbon dioxide from the atmosphere is key in climate change mitigation pathways. Well planned forest industry related measures can significantly increase carbon sequestration in living biomass as well as in harvested wood products. In our study we investigated the climate change mitigation effects of forest management systems and nature conservation conducting a Greenhouse Gas Inventory-like analysis on Hungarian forests using a forest management system and protection status specific breakdown and considering only the biomass pool. Our main conclusion was that under similar yield class distribution logging intensity and carbon sequestration are not inversely proportional. We observed that non-protected forests achieve higher net carbon sink under a higher logging intensity. Regarding forest management systems we observed significantly higher net carbon sink under transitional forest management than what was found for all other management systems. Continuous cover management and non-production forest management did not show significantly different carbon fluxes.